The corporal distribution and seasonal dynamics of the larva of Dermatobia hominis cattle treated and nontreated with flowers of sulphur - Gomes, Alberto; Sousa, Júlio C. de; Resende, Acylino M.; Curvo, João B. E. (Pesquisa Agropecuaria Brasileira, 2014)
In order to test the larvicidal activity of flowers of sulphur in the control of "berne" (larva of Dermatobia hominis), 50 male yearlings were supplied with a mineral supplement containing 13.289% of basic sulphur for 14 months. Another group, also 50 male yearlings, received common salt with phosphorus. Larvae were counted monthly on one side of each animal and their distribution was mapped. Monthly indices of infestation by "berne" were similar throughout the trial for treated and nontreated groups, and no statistical difference (P >0.05) was found when analysed by the Tukey test. There was much monthly variation in the infestations with main intensity in September and October, and this differed statistically (P <0.05) by the Waller-Duncan test to that of the other months. The body regions with the main incidence of "berne" were shoulder, trunk, head and neck, and hind-quarters, respectively, with no significant differences (P >0.05) in the degree of infestation during the months of major infestation (July, August, September and October). However, from November onwards, when lower infestation rates occurred, a significant difference (P <0.05) was observed, with the shoulder and trunk having the highest infestations. The results obtained suggest that, under these experimental conditions, flowers of sulphur did not show a larvicidal effect on the parasite populations and therefore the addition of sulphur in mineral supplements is not an efficient method of controlling this ectoparasite.